Healthy hands: development and evaluation of a knowledge transfer program - Mohamed @ Abd Aziz, Nurul Azmawati; Tengku Jamaluddin, Tengku Zetty Maztura; Ismail, Zarini; Mohd Rani, Mohd Dzulkhairi; Ramli, Shalinawati; Faroque, Habibah; Abd Samad, Farishah Nur; Ariffien, Abdul Rasyid; Che Amir Farid, Aisyah Ar Redha; Che Isahak, Che Ilina (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Children in pre-schools are at high risk of getting infections due to overcrowding, minimal awareness of basic hygiene and lack of immunity against microorganisms. Hand hygiene practice should be started at home where parents set good example, followed by formal education in pre-schools, primary and secondary school. This study aimed to develop a comprehensive program on hand hygiene practice in pre-schools. This paper presents the developmental aspects of the program material and the results of its evaluation process in a selected pre-school. Methods: Stage of development involved preparation of song, lyric, video clip, infographic and tablet application. The module was introduced during an intervention day called ‘Healthy Hands’ day. The acceptance of the module was evaluated before and after the intervention day. Evaluation was done by assessing pre-school children by face-to-face interview about knowledge on hand hygiene techniques and routine, such as before or after certain activities. Results: We managed to compose a song in three languages (Malay, English & Arabic), produced a video clip, an infographic and tablet application. A total of 227 children participated. Post intervention evaluation showed significant (p<0.001) increase of knowledge for eight out of eleven handwashing steps. The knowledge on hand hygiene routine i.e. after toilet, after playing outdoor, after sneezing and after playing with pet was also increased significantly. Conclusion: This comprehensive knowledge transfer program significantly improved the children’s hand hygiene techniques and routine and is recommended to be integrated into pre-school curriculum.